(812) The Application of Network Techniques in Planning and Management تطبيق تقنيات الشبكات في التخطيط والإدارة - Karl-Heinz Horn (INP, 2024)
The Study discusses the Critical Path Method (CPM) and the Program Evaluation and Review Technique (PERT), which are two modern mathematical planning methods. Both methods consist of two main parts: the network, which is the evident and intuitive part, and the mathematical model. The key difference is that CPM is a strictly determined model with fixed data, while PERT is a stochastic model where data are not always precisely determined but result from probability calculations. Network techniques can be applied in cases requiring planning and controlling processes made up of numerous parts, meaning processes that can be subdivided into activities or jobs. To find the shortest possible time to implement the entire set of activities, one must solve the succession problem and understand the relationships and interdependencies between all activities. One of the major advantages of network techniques is the ability to calculate a complete time schedule, including the exact dates for the beginning and finishing of each activity.